Risk Factors of anemia in head and neck cancer patients undergoing chemotherapy with high-dose cisplatin (Medical Journal of Indonesia, 2008)
Cisplatin is well-known for its effectiveness treatment against cancer, as well as its toxicity to human tissues. Of several documented side effects, anemia was reported to have significant association with decreased quality of life. This study was conducted to investigate development of cisplatin-induced anemia, and to identify independent factors contributing to anemia. Clinical data from head and neck cancer patients treated with high-dose cisplatin between December 2002 and December 2005 were obtained in this study. Incidence and risk factors of anemia were assessed in a model including age, sex, baseline hemoglobin level, baseline creatinine clearance, and occurrence of distant metastases. Multivariate logistic regression was used to define independent predictors of anemia. Among 86 eligible patients, 26 (30.2%) developed anemia, defined as Hb level lower than 11 g/dL. Age > 55 years old (RR = 2.2, 95% CI, 1.2-4.0), female sex (RR = 2.0, 95% CI, 1.2-3.8), baseline Hb â¤ 13 g/dL (RR = 4.2, 95% CI, 1.9-9.4) and baseline CrCl < 50 mL/min (RR = 2.9, 95% CI, 1.7-5.1) were significantly correlated with incidence of anemia (P < 0.05). In multivariate analysis, baseline Hb and baseline CrCl were identified as independent risk factors for anemia. However, considerable confounding was observed in baseline CrCl after stratified by age (aRR = 2.2, 95% CI, 1.1-4.7). Thus, baseline Hb level was the strongest predictor of anemia. The findings suggested that baseline Hb and CrCl were useful to recognize cisplatin-treated patients at risk for anemia who might benefits from preventive measures. (Med J Indones 2008; 17: 248-54)Keywords: anemia, cisplatin, chemotherapy, hemoglobin, creatinine clearance